Specimen Preparation Techniques for Testing Fully and Partially Saturated Sands in Dynamic Simple Shear (DSS) Test Device with Confining Pressure - Gulen, Derya Burcu; Eseller-Bayat, E. Ece (Springer International Publishing, 2017)
In this study, specimen preparation techniques for testing fully and partially saturated specimens were investigated. Various techniques were evaluated for obtaining loose to dense fully saturated sand specimens in a flexible membrane of DSS-C device, with minimal distortion to the specimen. Moist undercompaction technique in stages and then saturation with back pressure seem to be the best technique for obtaining loose to dense fully saturated uniform sand specimens. Gas/air entrapped partially saturated sand specimens were prepared by using a chemical powder: sodium percarbonate. The powder was mixed with water and predetermined amount of dry sand was rained into this solution. The chemical powder gets into reaction with water and generates oxygen gases which get entrapped in the sand voids. The techniques developed for obtaining uniform, repetitive sand specimens practically were discussed herein. The specimens prepared were tested under undrained conditions in Dynamic Simple Shear with Confining Pressure (DSS-C) testing device.